Особенности трудовых взаимоотношений и типичные правонарушения в сфере трудового законодательства (на примере Ставропольского края) - Черномордов, Л.И.; Журавлева, Е.П. (Культура народов Причерноморья, 2013)
В статье рассмотрена ситуация на рынке труда России, в том числе результаты
надзорно-контрольной деятельности за соблюдением законодательства о труде Ставропольского края.
Рассмотрены вопросы трудовых взаимоотношений между работником и работодателем, основные
направления деятельности сотрудника кадровой службы, определены типичные нарушения при
проверке соблюдения трудового законодательства, и в целях обеспечения качественного персонала даны
рекомендации по выработке кадровой стратегии. Сделаны выводы о необходимости правового
регулирования отношений, возникающих в сфере труда. У статті розглянута ситуація на ринку праці Росії, в тому числі результати наглядово-
контрольної діяльності за дотриманням законодавства про працю Ставропольського краю. Розглянуто
питання трудових взаімоотношеній між працівником і роботодавцем, основні напрямки діяльності
співробітника кадрової служби, визначені типові порушення при перевірці дотримання трудового
законодавства, і з метою забезпечення якісного персоналу дано рекомендації з вироблення кадрової
стратегії. Зроблено висновки про необхідність правового регулювання відносин, що виникають у сфері
праці. The article describes the situation on the Russian labor market, including the results of supervision
and control of the compliance with the labor legislation of the Stavropol Territory. The necessity of the
organization effectively operating infrastructure of the labor market, which should include three levels: national,
regional, enterprise-level. The problems of labor mutually ¬ interrelations between the employee and the
employer, the main activities of personnel officers, identified typical violations when checking compliance with
labor laws, and to ensure quality staff recommendations for the development of human resources strategy, which
allows the most effective way to realize global challenges the organization at every stage of its operations. And
all meropriya-making must be linked to the specific ¬ Coy basic HR processes in the organization - the
selection, evaluation, development and motivation. The enterprise must be developed labor standards for those
types of produc ¬ governmental operations that it performs. It is concluded that the relations arising in the
workplace, require legal regulation, the effectiveness of which largely determines the level of development of
society. At present, adopt the necessary measures working model of health and safety. In its place has come ¬
tion system control occupational hazards. Pa ¬ employers to identify, assess and implement measures to reduce
them